Sleep Disorder Prevalence and Influencing Factors in Children with Cerebral Palsy - Uni Gamayani; Milda Aryani; Nushrotul Lailiyya; Iin Pusparini (Universitas Islam Bandung, 2022)
Children with cerebral palsy are considered a population at risk for sleep disturbance. Various factors can cause sleep disorders in children with cerebral palsy. This study investigates the relationship between endogenous factors and sleep disorders in children with cerebral palsy. It was a cross-sectional analytical study using randomized sampling on children with cerebral palsy who met the inclusion criteria for the period of May–August 2017. The location of the study was special schools in the Bandung area, Indonesia. All participants were screened with the Sleep Disturbances Scale for Children (SDSC) questionnaire to determine the prevalence of period of sleep disorders. Data analysis was then performed using the unpaired t test to compare the characteristics of two variables with a p value≤0.05 considered statistically significant. Sixty-six subjects aged 8–14 years were recruited. The results showed that the prevalence of sleep disorders was 67% (32 children), with insomnia as the most common type of sleep disorder (39%). There was a significant association between motor disabilities type and sleep disorders (p≤0.05). The most common type of sleep disorder in children with cerebral palsy is insomnia. In conclusion, there is a relationship between motor disability type and sleep disorders in cerebral palsy children.